Penguatan Regulasi Emosi Santri melalui Teknik Emotional Journaling di Pondok Pesantren Tahfidz Barokah Merapi Magelang Regulasi Emosi Santri melalui Teknik Emotional Journaling di Pondok Pesantren Tahfidz Barokah Merapi Magelang: Penguatan Regulasi Emosi Santri melalui Teknik Emotional Journaling di Pondok Pesantren Tahfidz Barokah Merapi Magelang Regulasi Emosi Santri melalui Teknik Emotional Journaling di Pondok Pesantren Tahfidz Barokah Merapi Magelang - Niken Setyaningrum; Ardhian Indra Darmawan; Fitriah M Suud; Mirawati (Ruang Ide Publisher, 2026)
Adolescents living in Islamic boarding schools often face various academic demands, religious activities, and social adjustments that may trigger diverse emotional experiences. Therefore, emotional regulation becomes an important skill that needs to be developed among students to help them manage emotional experiences adaptively. This community service activity aimed to strengthen students’ emotional regulation through emotional journaling training. The activity was conducted at Pondok Pesantren Tahfidz Barokah Merapi, Magelang, involving 50 students as participants. A quantitative approach with a pre-test and post-test design was employed. Emotional regulation was measured using the Cognitive Emotion Regulation Questionnaire (CERQ) before and after the intervention. Data were analysed using the Wilcoxon Signed-Rank Test to examine differences in emotional regulation scores before and after the activity. The results indicated an improvement in emotional regulation scores following the emotional journaling training. In addition, the distribution of emotional regulation categories showed an increase in the proportion of participants in the high category and a decrease in the low category. Statistical analysis also revealed a significant difference between pre-test and post-test scores. These findings suggest that emotional journaling can serve as an effective reflective strategy to help students recognize, express, and manage their emotions more adaptively. This activity is expected to provide an alternative approach to support the psychological well-being of students in Islamic boarding school environments.